From the Thyroid to the Heart (Global Journal of Medical Research, 2023)
The pathogenesis of human disease is commonly considered to be unique to each organ or system This has led to specialization in medical practice leaving little space for global pathogenesis concepts In this review we have departed from a biochemical concept of coenzyme Q10 CoQ10 deficiency and its relation to the initiation of hypoxia response in a systemic way Several conditions of secondary CoQ10 deficiency are known in the literature by which the organs involved could be affected by hypoxia and switch to glycolytic metabolism The most salient biomarkers of this situation are the low T3 syndrome and the elevation of IL-6 These parameters together with CoQ10 deficiency delineate a condition of acquired mitochondrial dysfunction Additional related biochemical deficiency conditions affect magnesium selenium and iron levels Visualization of glycolysis can be clearly achieved by diagnostic imaging methods based on the use of 18F-fluoro-deoxyglucose 18F-FDG We present several examples of diagnostic imaging with 18F-FDG to demonstrate our model of acquired mitochondrial dysfunction and disease